(untitled) (Current Horticulture, 2024)
The experiment was conducted to standardize the method and time of propagation of avocado (Persea americana Mill) through vegetative means at CHES, ICAR-IIHR, Chettalli, during 2012-13. There were four methods of multiplication i.e. veneer grafting, cleft grafting, T-budding and patch budding, performed throughout the year. After 90 days of grafting, mean success was highest in cleft grafting (32.5%), followed by veneer grafting (8.3%), T-budding (7.5%) and patching budding (5.8%). There was highest mean success during September (32.5%), followed by 22.5 per cent during March and August 2012. Among different combinations of months and propagation methods, highest success (70%) was recorded in cleft grafting performed during September 2012. This was closely followed by same method done during March 2012 (60%). The success in cleft grafting was higher than other three methods throughout 2012-13. The growth of the scion was higher in grafting methods than budding methods. The transplantable seedlings after one year were highest (60%) in cleft grafting done September 2012. Thus, cleft grafting during September and March was found most suitable for vegetative propagation of avocado under humid tropical conditions.